2010
DOI: 10.1038/nrc2809
|View full text |Cite
|
Sign up to set email alerts
|

Eicosanoids and cancer

Abstract: Eicosanoids, including prostaglandins and leukotrienes, are biologically active lipids that have been implicated in various pathological processes, such as inflammation and cancer. This Review highlights our understanding of the intricate roles of eicosanoids in epithelial-derived tumours and their microenvironment. The knowledge of how these lipids orchestrate the complex interactions between transformed epithelial cells and the surrounding stromal cells is crucial for understanding tumour evolution, progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
1,542
3
22

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,518 publications
(1,622 citation statements)
references
References 139 publications
28
1,542
3
22
Order By: Relevance
“…26 To give a few examples, PGE 2 , the main prostaglandin, has been reported to inhibit apoptosis in colon cancer 10 and in radiation-treated epithelial cells 11 through mechanisms involving the proteins of the Bcl-2 family. On the other hands, PGE 2 has been shown to induce apoptosis in human lymphocytes and in fibroblasts through multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…26 To give a few examples, PGE 2 , the main prostaglandin, has been reported to inhibit apoptosis in colon cancer 10 and in radiation-treated epithelial cells 11 through mechanisms involving the proteins of the Bcl-2 family. On the other hands, PGE 2 has been shown to induce apoptosis in human lymphocytes and in fibroblasts through multiple pathways.…”
Section: Discussionmentioning
confidence: 99%
“…22 Finally, most reports claim that PGE 2 skews the immune response towards a T h 2 response, although conflicting results have been reported. 16,23,24 Notably, the alleged Tcell stimulatory effect of PGE 2 has only been shown for CD4 1 T h 1 cells in vivo and in models of autoimmunity. In the current investigation, we show that a large fraction of blood CD4 1 and CD8 1 T cells were positive for the T h 1 marker T-bet, indicating that COX-2 inhibition and GM-CSF immunotherapy induce a T h 1 response.…”
Section: Short Reportmentioning
confidence: 99%
“…High levels of constitutive expression of COX-2 and its major product, PGE 2 , have been detected in various tumors, including CRC (Wang and DuBois, 2010a). PGE 2 is involved in tumor progression by inducing angiogenesis, invasion and metastasis in several solid tumors (Wang and DuBois, 2010b). Moreover, pharmacological, cell biological and gene targeting studies investigating COX-2 have demonstrated that PGE 2 produced through the COX-2-dependent pathway contributes to the progression of several types of cancer (Tsujii and DuBois, 1995;Tsujii et al, 1998).…”
Section: Introductionmentioning
confidence: 99%